Healthcare workers' perspectives on access to sexual and reproductive health services in the public, private and private not-for-profit sectors: insights from Kenya, Tanzania, Uganda and Zambia - Gaby I. Ooms; Janneke van Oirschot; Dorothy Okemo; Tim Reed; Hendrika A. van den Ham; Aukje K. Mantel-Teeuwisse (BMC, 2022)
Abstract Background Access to sexual and reproductive health services remains a challenge for many in Kenya, Tanzania, Uganda and Zambia. Health service delivery in the four countries is decentralised and provided by the public, private and private not-for-profit sectors. When accessing sexual and reproductive health services, clients encounter numerous challenges, which might differ per sector. Healthcare workers have first-hand insight into what impediments to access exist at their health facility. The aim of this study was to identify differences and commonalities in barriers to access to sexual and reproductive health services across the public, private and private not-for-profit sectors. Methods A cross-sectional survey was conducted among healthcare workers working in health facilities offering sexual and reproductive health services in Kenya (n = 212), Tanzania (n = 371), Uganda (n = 145) and Zambia (n = 243). Data were collected in July 2019. Descriptive statistics were used to describe the data, while binary logistic regression analyses were used to test for significant differences in access barriers and recommendations between sectors. Results According to healthcare workers, the most common barrier to accessing sexual and reproductive health services was poor patient knowledge (37.1%). Following, issues with supply of commodities (42.5%) and frequent stockouts (36.0%) were most often raised in the public sector; in the other sectors these were also raised as an issue. Patient costs were a more significant barrier in the private (33.3%) and private not-for-profit sectors (21.1%) compared to the public sector (4.6%), and religious beliefs were a significant barrier in the private not-for-profit sector compared to the public sector (odds ratio = 2.46, 95% confidence interval = 1.69-3.56). In all sectors delays in the delivery of supplies (37.4-63.9%) was given as main stockout cause. Healthcare workers further believed that it was common that clients were reluctant to access sexual and reproductive health services, due to fear of stigmatisation, their lack of knowledge, myths/superstitions, religious beliefs, and fear of side effects. Healthcare workers recommended client education to tackle this. Conclusions Demand and supply side barriers were manifold across the public, private and private not-for-profit sectors, with some sector-specific, but mostly cross-cutting barriers. To improve access to sexual and reproductive health services, a multi-pronged approach is needed, targeting client knowledge, the weak supply chain system, high costs in the private and private not-for-profit sectors, and religious beliefs.